2009
DOI: 10.1007/s00330-009-1524-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound demonstration of distal biceps tendon bifurcation: normal and abnormal findings

Abstract: We demonstrate the US appearance of the distal biceps tendon bifurcation in normal cadavers and volunteers and in those affected by various disease processes. Three cadaveric specimens, 30 normal volunteers, and 75 patients were evaluated by means of US. Correlative MR imaging was obtained in normal volunteers and patients. In all cases US demonstrated the distal biceps tendon shaped by two separate tendons belonging to the short and long head of the biceps brachii muscle. Four patients had a complete rupture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 14 publications
3
64
0
1
Order By: Relevance
“…In light of these predisposing factors for a distal biceps tendon injury, it is exceedingly rare to see distal biceps tendon injury in the young population. Partial tears of distal biceps tendon may be traumatic or attritional and usually involve only one of the components of biceps tendon (short head or long head) [4]- [6]. Our patient did not recall any history of trauma.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In light of these predisposing factors for a distal biceps tendon injury, it is exceedingly rare to see distal biceps tendon injury in the young population. Partial tears of distal biceps tendon may be traumatic or attritional and usually involve only one of the components of biceps tendon (short head or long head) [4]- [6]. Our patient did not recall any history of trauma.…”
Section: Discussionmentioning
confidence: 89%
“…Partial tears involving the long head of biceps tendon usually presents with a typical Popeye sign which is a soft tissue lump over the anterior aspect of the middle third of arm, suggesting retraction of belly of biceps which was not seen in our patient [4]. Sometimes the symptoms of partial biceps tendon tear may even mimic or co-exist with conditions like bicipital tendinosis, leading to missed or delay in the diagnosis of chronic distal biceps tendon tear [17].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recent anatomical studies have demonstrated that the distal biceps brachii tendon consists of two separate tendons rather than a single tendon as previously thought. Tagliafico and co-workers assessed the sonographic appearance of the distal biceps tendon bifurcation in healthy volunteers and in patients with tear of the distal biceps tendon and correlated the sonographic findings with MRI [5]. In their study, ultrasound demonstrated the two separate tendons of the distal biceps tendon in all volunteers and patients and was able to differentiate between complete tendon rupture, partial tear of the short and long head of the biceps tendon.…”
Section: Musculoskeletal Ultrasoundmentioning
confidence: 99%
“…An Italian-Canadian study [1] has shown that the distal insertion of the tendon on the radial tuberosity is bifurcated; the presence of a bursa allows it to slide smoothly around the tuberosity during pronation-supination of the forearm. In addition to this bifid tendon, there is a third distal structure known as the Lacertus fibrosus, or bicipital aponeurosis, which detaches from the medial aspect of the tendon, crosses over the median artery and median nerve, and inserts onto the superficial aponeurosis of the flexor muscles.…”
Section: Introductionmentioning
confidence: 99%